Repair of Scimitar syndrome using an extracardiac conduit in pediatric patients: Report of two patients - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2019)
Scimitar syndrome (SS) can be repaired by different surgical techniques including direct implantation, intracardiac rerouting, and in situ pericardial channel to direct the Scimitar vein (SV) to the left atrium. The presence of several anatomical variations such as remote infradiaphragmatic drainage of the SV and abnormal situs makes the repair more challenging with conventional repair techniques. In this paper, we present our experience in using an extracardiac-ringed polytetrafluoroethylene conduit in two pediatric patients (14 months and 2 years old) with SS.
Keywords: Pulmonary vein; Scimitar syndrome; extracardiac conduit